Hometown legend - Jenkins, Jerry B. (New York : Warner Books, 2001)
Athens City, Alabama, is a town that lost its heart the day the high school football team lost the state championship & suffered a tragedy. Since that night, the town that once enjoyed superstar status has fallen on hard times. Now, years later, the former coach returns to head up one final season aided by a local who tells the story with a fresh voice. Together, they fight Goliath & learn that love & reconciliation are more important than winning ever could be. It is heartwarming storytelling that Jenkins fans have come to love.
Keywords: Football coaches -- Fiction; High school students -- Fiction; Parent and child -- Fiction; Football players -- Fiction; School sports -- Fiction; Alabama -- Fiction; Domestic fiction; Football stories; Bildungsromans